Artesunate/mefloquine treatment of multi-drug resistant falciparum malaria. - Price, R; Nosten, F; Luxemburger, C; van Vugt, M; Phaipun, L; Chongsuphajaisiddhi, T; White, N (1997)
On the western border of Thailand, in an area endemic for multi-drug resistant Plasmodium falciparum malaria, therapeutic responses were assessed in 1967 patients with uncomplicated falciparum malaria treated with 3 d of artesunate (total dose 12 mg/kg) plus mefloquine (total dose 25 mg/kg). The regimen was well tolerated and resulted in a rapid clinical response; within 48 h, 96% of patients were aparasitaemic and 94% were afebrile. After correcting for reinfections, the cure rate by day 42 was 89% (95% confidence interval [95% CI] 87-91%). Three independent factors were found to predict recrudescence: age < 14 years (adjusted hazards ratio [AHR] = 1.6, 95% CI 1.1-2.3), initial parasitaemia greater than > 40,000/microL (AHR = 1.6, 95%, CI 1.2-2.2), and pure P. falciparum infections (AHR = 1.8, 95% CI 1.3-2.7). These 3 factors combined accounted for 62% of all treatment failures. Patients who received mefloquine on admission with a high admission parasitaemia (> 40,000/microL) had a three-fold (95% CI 1.3-7) risk of subsequent recrudescence compared with those who received their mefloquine on the second or third day (P = 0.01). There has been no decline in the efficacy of the 3 d artesunate plus mefloquine regimen since it was introduced in 1992. This regimen is safe, well tolerated, and highly effective in the treatment of multi-drug resistant falciparum malaria.